Little Big Team: Acquiring Human Capital in Software Startups - Seppänen, Pertti; Liukkunen, Kari; Oivo, Markku (Product-Focused Software Process Improvement, 2017)
Background – Resource-based-view and human capital theories have been used for decades when studying firms, their strategies, organizations, businesses, and successes. The value of the theories as general frameworks has commonly been recognized, especially because of their flexibility in adopting new perspectives, such as the dynamic character of the resources and human capital. Startup companies represent an interesting area on a map of firms because of their specific characteristics and tendency not to strictly follow the processes common in more established companies. Despite the differences, it is reasonable to assume that startups face similar phenomena as established companies do when building up their firms and operations. Aim – In this research, we studied software startups from the perspective of resource-based-view and human capital theories. We examined what human capital resources, capabilities, knowledge, and skills, were needed in the early stages of software startups and how the startups acquired such human capital. Method – We conducted a multiple-case study on a group of software startups in Norway and Finland. Results – We identified six high-level capability areas, nine means to acquire those capabilities, and nine drivers affecting the utilization of different means. We concluded that the capabilities in software startups are dynamic, evolving by growth and learning from the basis of the founders’ prior capabilities, and the utilization of different acquiring means is a case-dependent thing with a varying set of drivers. We also found the uniqueness of the resources, as proposed by the resource-based-view theory, was not reached in our case startups, but replaced with a combination of commonly-available resources, innovation, and application-specific capabilities.